THEORETICAL APPROACHES TO THE PROBLEM OF INCREASING TRANSPORT EFFICIENCY - Babenko, S. O. (Science and Transport Progress, 2008)
In the article the directions of decrease of the operational expenses and, as a result, the cost price of transportations due to reduction of a part of administrative expenses in cost prices of transportation of cargoes and passengers, the growth of labour productivity and the reduction of personnel contingent according to the volume of transportations are considered.